The Relationship between Knowledge Management Practices and Technological Innovation: A Conceptual Framework - Pei-Lee Gan; Alex Tun-Lee Foo; Voon-Hsien Lee; Yin-Kuan Ng (International Journal of Management, Knowledge and Learning, 2012)
This research paper aims to establish a conceptual framework that links thedifferent dimensions of knowledge management, namely knowledge acquisition,knowledge dissemination and knowledge application, with innovationperformance, particularly focusing on technological innovation (i. e. productand process innovation). This study seeks to benefit the top managementteam of any organization that desires to enhance and improve their level oftechnological innovation through the effective implementation of the relevantKM dimensions The findings of this study conclude that the effectual useof knowledge management practices is believed to unlock the technologicalinnovation of a firm.